Modelling molecular structure and reactivity in biological systems - Naidoo, Kevin J. (Royal Society of Chemistry, 2006)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Computational and theoretical tools for understanding biological processes at the molecular level is an exciting and innovative area of science. Using these methods to study the structure, dynamics and reactivity of biomacromolecules in solution, computational chemistry is becoming an essential tool, complementing the more traditional methods for structure and reactivity determination. Modelling Molecular Structure and Reactivity in Biological Systems covers three main areas in computational chemistry; structure (conformational and electronic), reactivity and design. Initial sections focus on the link between computational and spectroscopic methods in the investigation of electronic structure. The use of Free Energy calculations for the elucidation of reaction mechanisms in enzymatic systems is also discussed. Subsequent sections focus on drug design and the use of database methods to determine ADME (absorption, distribution, metabolism, excretion) properties. This book provides a complete reference on state of the art computational chemistry practised on biological systems. It is ideal for researchers in the field of computational chemistry interested in its application to biological systems.
"The proceedings of the WATOC 2005, Modelling Structure and Reactivity meeting held in Cape Town, South Africa, 16-21 January 2005"--T.p. verso. "7th triennial conference of the World Association of Theoretical and Computational Chemists (WATOC 2005) in Cape Town, South Africa"--Pref.
Keywords: Chemistry, Physical and theoretical -- Congresses.; Molecular structure -- Congresses.; Molecular structure -- Computer simulation -- Congresses.; Reactivity (Chemistry) -- Congresses.; Reactivity (Chemistry) -- Computer simulation -- Congresses.; Biological systems -- Congresses.; elektronické knihy; electronic books